Respuesta :
Answer:
[tex](f-g)(4) = -59[/tex]
Step-by-step explanation:
We are given the two functions:
[tex]f(x)=4x-3\text{ and } g(x) = x^3 +2x[/tex]
And we want to find the value of:
[tex](f-g)(4)[/tex]
Recall that this is equivalent to:
[tex](f-g)(4) = f(4) - g(4)[/tex]
Find f(4):
[tex]f(4) = 4(4)-3 = 13[/tex]
And find g(4):
[tex]g(4) = (4)^3 + 2(4) =72[/tex]
Substitute:
[tex](f-g)(4) = (13)-(72)[/tex]
And subtract. Hence:
[tex](f-g)(4) = -59[/tex]
Step-by-step explanation:
I love this question!
So there are a couple different ways of solving this. You feel free to ignore whichever one makes less sense.
Subtracting First
The first option is taking f(x) and g(x) and subtracting them, then introducing the number.
The calculation:
f(x) - g(x)
Substitute.
4x - 3 - (x^3 + 2x)
Multiply out the negative.
4x - 3 - x^3 - 2x
Rewrite.
-x^3 + 4x - 2x - 3
Simplify.
-x^3 + 2x - 3
Then, replace x with 4.
-(4)^3 + 2(4) - 3
Simplify.
-64 + 8 - 3
Add.
-59
Making x = 4 first
Here, we'll do what's on the tin. Find f(4) and g(4), then subtract them.
f(x) = 4x - 3
f(4) = 4(4) - 3
f(4) = 16 - 3
f(4) = 13
Then find g(4):
g(x) = x^3 + 2x
g(4) = (4)^3 + 2(4)
g(4) = 64 + 8
g(4) = 72
Then, subtract these two:
f(4) - g(4) = 13 - 72
f(4) - g(4) = -59
Answer:
Either way, the answer is -59